Heterogeneity in Damages from a Pandemic - Finkelstein, Amy; Kocks, Geoffrey; Polyakova, Maria; Udalova, Victoria (The Review of Economics and Statistics, 2024)
We use linked survey and administrative data to document differences across multiple socio-economic and demographic groups in the extent of adverse economic and health impacts of the first two years of the COVID-19 pandemic in the United States. Across a wide set of characteristics-including race/ethnicity, education, industry, and occupation-the impacts of the pandemic on all-cause mortality and on employment were disproportionately concentrated in the same groups in the population. As the pandemic progressed, disparities in the pandemic's mortality impacts narrowed substantially between Black and White Americans and between Hispanic and White Americans, but persisted along the educational divide. For economic damages, only Hispanic-White disparities narrowed; Black-White and educational disparities persisted for the first two years of the pandemic. We also document greater mortality impacts for lower income individuals, with this negative income-excess mortality gradient becoming steeper in the pandemic's second year. Together our findings-using a consistent set of methods and measures on nationally representative data with a wide set of measures of socio-economic status-paint a detailed picture of the heterogeneous impacts of the first two years of the COVID-19 pandemic on health and economic well-being.